European union standards for tuberculosis care - Migliori, G B; Zellweger, J P; Abubakar, I; Ibraim, E; Caminero, J A; De Vries, G; D'Ambrosio, L; Centis, R; Sotgiu, G; Menegale, O; Kliiman, K; Aksamit, T; et al. (The European respiratory journal, 2012)
The European Centre for Disease Prevention and Control (ECDC) and the European Respiratory Society (ERS) jointly developed European Union Standards for Tuberculosis Care (ESTC) aimed at providing European Union (EU)-tailored standards for the diagnosis, treatment and prevention of tuberculosis (TB). The International Standards for TB Care (ISTC) were developed in the global context and are not always adapted to the EU setting and practices. The majority of EU countries have the resources and capacity to implement higher standards to further secure quality TB diagnosis, treatment and prevention. On this basis, the ESTC were developed as standards specifically tailored to the EU setting. A panel of 30 international experts, led by a writing group and the ERS and ECDC, identified and developed the 21 ESTC in the areas of diagnosis, treatment, HIV and comorbid conditions, and public health and prevention. The ISTCs formed the basis for the 21 standards, upon which additional EU adaptations and supplements were developed. These patient-centred standards are targeted to clinicians and public health workers, providing an easy-to-use resource, guiding through all required activities to ensure optimal diagnosis, treatment and prevention of TB. These will support EU health programmes to identify and develop optimal procedures for TB care, control and elimination.